2018
DOI: 10.1089/aid.2018.0049
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New HIV-1 CRF01_AE/CRF07_BC Recombinant Virus Form Among Men Who Have Sex with Men in Beijing, China

Abstract: Recent studies have revealed that three major viral strains (CRF07_BC, CRF01_AE, and subtype B) have been cocirculating among men who have sex with men in Beijing. Cocirculation of multiple subtypes in the same population contributes significantly to the emergence of recombinant viruses. This study reports a near full-length genome of a novel, second-generation HIV-1 recombinant (BJ2015EU16) between CRF07_BC and CRF01_AE. The analysis of BJ2015EU16 shows that the genome comprises three interlaced segments, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Jiao et al . [ 8 ] reported that the Beijing BJ2015EU16 strain includes two CRF07_BC and one CRF01_AE fragments, with CRF07_BC as the backbone and two recombination breakpoints in the vpu and env genes. Zhou et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Jiao et al . [ 8 ] reported that the Beijing BJ2015EU16 strain includes two CRF07_BC and one CRF01_AE fragments, with CRF07_BC as the backbone and two recombination breakpoints in the vpu and env genes. Zhou et al .…”
mentioning
confidence: 99%
“…In recent years, countless URFs derived from CRF01_AE and CRF07_BC have been reported in Hebei, Beijing, and Tianjin [6][7][8][9]. Among the four CRF01_AE/CRF07_BC recombinants reported in Hebei Province, two used CRF01_ AE as the backbone to insert four CRF07_BC fragments, and two used CRF07_BC as the backbone to insert three and four CRF01_AE fragments, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation